Response Time, Sarana dan Prasarana Pergudangan dan Diklat Search And Rescue (SAR) Terhadap Efektivitas Kerja Misi Operasi SAR di Badan SAR Nasional - Paul Sipoh Hutahuruk; Chandra Kresna Riyanto; Sudjanadi Cipto (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2019)
The study was conducted at Badan SAR Nasional using quantitative method, with the number of samples taken based on Slovin formula as many as 40 people. The study used linear regression analysis, simple, partial or simultaneous correlation and path analysis. The results conclude that there is influence of Quality Relation Response Time Service, Facilities & Infrastructure Warehousing and Training Search And Rescue (Sar) to Work Effectiveness SAR Operations Mission  In Badan SAR Nasional.